Family Empowerment in Monitoring Fe Provision To (Rematri) Adolescent Women as A Stunting Prevention Effort - Yuningsih, Nani; Rohaeti, Ayi Tansah; Sutomo, Omo (Jurnal Menara Pengabmas, 2023)
The prevalence of stunting is around 27.67% (2019 Indonesian Toddler Nutrition Status Survey), a problem in health development. Presidential Decree no.18 of 2020 RPJMN 2020 – 2024. 4th pont strategy, improving the quality of children, women and youth. Preventing stunting can be done in this cycle. is about FE supplementation for teenagers, in Banten province children with stunting conditions there are 8.7% Lebak district 5.03% in 2022, in PKM Kalanganyar 1.55% with adherence to drinking Fe among Rematri (Adolescent Girls) is still low for those in home aged 12 – 18 years. In Sangiangtanjung Village Solution, determining targets for 50 Rematri families, licensing, coordination between Kesbangpol, health service, community health center, village. Resource persons, activity schedule, results obtained pre and post education. Family Knowledge of Giving Fe to Rematri has an increase in the minimum and maximum scores from 1 – 8 to 6 – 10, almost all (96.0%) there is an increase in knowledge scores, the p value = 0.000 (p < α) is considered significant. The minimum and maximum Hb values ​​increased after administration of Fe tablets from 10.4 – 13.5mg% to 11.0 – 13.8mg%. This means giving Fe tablets for 4 weeks at a dose of 1 x 1 tablet 60 mg once every 1 week. The activity is in synergy with the community health center program with the monthly activity of providing Rematri Fe, which is a nutrition program at the Community Health Center.